Multilingualism In Yogyakarta’s Tourism: The Role Of English, French, And Japanese In Enhancing Visitor Experience - Ferhadius Endi; Dian Lestari; Weka Kusumastiti; Annisaa Nurul Atiqah (Journal of Education, Humaniora and Social Sciences (JEHSS), 2026)
This study aims to investigate the representation of English, French, and Japanese in Yogyakarta’s tourism signage, focusing on Malioboro and Pentingsari Tourism Village, and explores the implications for visitor experience and cultural commodification. This study employs a qualitative approach, synthesizing secondary data from prior linguistic landscape studies in Yogyakarta, statistical reports, and global tourism literature. Drawing on statistical data, prior studies, and global comparisons, the findings reveal significant gaps: English signage is limited to 15% in Malioboro and 3.6% in Pentingsari, despite 70% of international tourists preferring it, while French and Japanese are absent despite notable visitor numbers (3,072 and 2,262 in 2024, respectively). These gaps hinder navigation, cultural immersion, and economic potential, particularly for Micro and Small Enterprises (MSEs) reliant on tourism. The study proposes three strategies—enhanced multilingual signage, language training for guides, and technology integration—to optimize communication, enhance visitor experience, and drive economic growth, which reached 14.21% in 2023. By targeting underserved markets like French and Japanese tourists, Yogyakarta can balance local identity with global accessibility, fostering sustainable tourism development.